Vocational integrity. Issue 2 (19th June 2018) - Cummings, Orin W.
Abstract: Luther's doctrine of vocation is about faithfully living the baptismal life. This article argues that for the Christian a theology of work—vocation—is not to be constricted to the spiritual sphere only. The Christian is called from the temporal sphere, but not out of it. As such, the Christian embraces the spiritual and temporal spheres in response to God's grace and for the good of the neighbor.